Proton Conducting Solid Polymer Electrolytes Based Carboxymethyl Cellulose Doped Ammonium Chloride: Ionic Conductivity And Transport Studies - Nur Hidayah Binti Ahmad; Mohd Ikmar Nizam Mohamad Isa (Central Institute of Plastics Engineering & Technology, 2024)
The present work focuses on the preparation of solid polymer electrolytes (SPEs) based carboxymethyl cellulose, CMC as host polymer doped with ammonium chloride, AC (0–20 wt.%) as ionic dopant via solution casting technique. The ionic conductivity and transport parameter of SPEs films were analyzed using electrical impedance spectroscopy in the frequency range of 1 Hz–50 MHz at selected temperature of 303–383 K. The highest ionic conductivity of 1.43 × 10−3 S/cm was obtained at 16 wt.% AC. Temperature-dependent ionic conductivity showed that the ionic conductivity obeys Arrhenius rule where R2~1 and thermally assisted. Transport studies showed that the ionic conductivity was influenced by the ionic mobility and diffusion coefficient.